Analisa Keberhasilan Proyek Perumahan Persadamas Di Banjarmasin - Candra Yuliana (INFO-TEKNIK, 2003)
Persadamas Real Estate is pioneer housing for middle upper group in Banjarmasin founded PT. Ciptabangun Persadamas. Even though still in house developing nearly sold out. Because the reason above, is necessary recognized how to success PersadamasThe aim of this research to understanding important factors which influence house buyer decision, the strength and the weakness of Persadamas real estate, sales success and capital return analysis. Make structuring interview with developer and questionnaires to house owner.The important factors such as location, road width, housing infrastructure (water, electricity, and telephone) and public facilities (court sport, green area, school and security). Persadamas stay in number one compared than other housing real estate mainly in housing wide, electric and public facilities provided and also the amount of sales. Persadamas real estate sales in every year (1997 though 2002) reached determined target that is 25 unit/year, even overlap, except 1997. From analysis  capital return got project with net present value = Rp. 10.020.969.000,- with initial capital (100% equity) are Rp 3.795.000.000.-. Internal rate of return take place about 45,6289%. Capital return reached after sales for six years (1997-2002).